2014
DOI: 10.1037/a0035984
|View full text |Cite
|
Sign up to set email alerts
|

Text comprehension mediates morphological awareness, syntactic processing, and working memory in predicting Chinese written composition performance.

Abstract: The goal of the present study was to test opposing views about four issues concerning predictors of individual differences in Chinese written composition: (a) Whether morphological awareness, syntactic processing, and working memory represent distinct and measureable constructs in Chinese or are just manifestations of general language ability; (b) whether they are important predictors of Chinese written composition, and if so, the relative magnitudes and independence of their predictive relations; (c) whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 92 publications
(194 reference statements)
6
42
1
Order By: Relevance
“…Nevertheless, the research on reading and writing association in Chinese is not as systematic and extensive as that in English. Some researchers studied reading-to-writing relationship (Leong, Loh, Ki, & Tse, 2011;Lin et al, 2010;Qu, Damian, Zhang, & Zhu, 2011), whereas others studied writing-to-reading relationship (Chan, Ho, Tsang, Lee, & Chung, 2006;Guan et al, 2011, Guan, Ye, Wagner, & Meng, 2012, Guan, Ye, Meng, & Leong, 2013, Guan, Ye, Wagner, Leong, & Meng, 2014McBride-Chang et al, 2011Tan, Spinks, Eden, Perfetti, & Siok, 2005).…”
Section: Associations Between Reading and Writingmentioning
confidence: 99%
“…Nevertheless, the research on reading and writing association in Chinese is not as systematic and extensive as that in English. Some researchers studied reading-to-writing relationship (Leong, Loh, Ki, & Tse, 2011;Lin et al, 2010;Qu, Damian, Zhang, & Zhu, 2011), whereas others studied writing-to-reading relationship (Chan, Ho, Tsang, Lee, & Chung, 2006;Guan et al, 2011, Guan, Ye, Wagner, & Meng, 2012, Guan, Ye, Meng, & Leong, 2013, Guan, Ye, Wagner, Leong, & Meng, 2014McBride-Chang et al, 2011Tan, Spinks, Eden, Perfetti, & Siok, 2005).…”
Section: Associations Between Reading and Writingmentioning
confidence: 99%
“…Semantic radical representation was expected to be particularly important in reading comprehension because it facilitates the semantic representation (i.e., meaning) of the characters, which in turn facilitates text comprehension. Previous studies have found that word spelling is an important predictor of written composition (e.g., Yeung et al 2013bYeung et al , 2015, and that reading comprehension mediates morphological awareness, syntactic processing and working memory in predicting written composition (Guan, Ye, Wagner, Meng, & Leong, 2014). It was hypothesized in the present study that orthographic skills (semantic radical representation, phonetic radical representation and orthographic memory of radicals) would contribute to written composition indirectly through their effects on word spelling and reading comprehension.…”
Section: Aim Of the Present Studymentioning
confidence: 95%
“…As postulated in Model 1, the preferred model conceptualizing the interrelationships among the variables in the study based on the structural equation modeling results, orthographic skills contributed to written composition indirectly through their effects on word spelling and reading comprehension. In the recent study by Guan et al (2014), morphological awareness, syntactic processing and working memory made unique contributions to Chinese written composition, but their predictive relations were mediated by text comprehension performance. In the present study, other than reading comprehension, we also included word spelling.…”
Section: Orthographic Skills and Chinese Text Level Literacy Skillmentioning
confidence: 96%
“…Hoskyn and Swanson () also showed WM scores accounted for a significant amount of variance in writing, and the influence was maintained even when spelling, handwriting speed, digit span, word knowledge and reading comprehension skill were taken into account statistically. Furthermore, Guan et al () also showed that WM was the strongest predictor toward Mandarin‐speaking children's writing skills at Grades 4, 5 and 6.…”
Section: Working Memory and Writingmentioning
confidence: 96%